2018
DOI: 10.1111/ina.12517
|View full text |Cite
|
Sign up to set email alerts
|

Dampness and mold in homes across China: Associations with rhinitis, ocular, throat and dermal symptoms, headache and fatigue among adults

Abstract: We studied dampness and mold in China in relation to rhinitis, ocular, throat and dermal symptoms, headache and fatigue. A questionnaire study was performed in six cities including 36 541 randomized parents of young children. Seven self‐reported signs of dampness were evaluated. Multilevel logistic regression models were used to calculate odds ratios (ORs). Totally, 3.1% had weekly rhinitis, 2.8% eye, 4.1% throat and 4.8% skin symptoms, 3.0% headache and 13.9% fatigue. Overall, 6.3% of the homes had mold, 11.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 50 publications
(130 reference statements)
7
35
0
2
Order By: Relevance
“…16 However, previous studies have shown associations between snoring and other respiratory conditions such as asthma and chronic rhinosinusitis. [31][32][33] Zhang et al 34 showed an association between building dampness and non-respiratory symptoms such as eye and skin symptoms, headache and fatigue. An association between indoor dampness and insomnia symptoms has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, previous studies have shown associations between snoring and other respiratory conditions such as asthma and chronic rhinosinusitis. [31][32][33] Zhang et al 34 showed an association between building dampness and non-respiratory symptoms such as eye and skin symptoms, headache and fatigue. An association between indoor dampness and insomnia symptoms has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the total concentration of microbial volatile organic compounds (MVOCs), the microbial emissions, is almost four times higher than the average home level, and the levels of 2‐methyl‐1‐butanol and 3‐methyl‐1‐butanol were 15‐17 times higher compared to homes 7 . The exposure of indoor microbiome, mold, and MVOCs is suggested to be associated with asthma development and other respiratory symptoms, 8–10 rhinitis, eye irritation, skin itching and redness, headache, and tiredness 11–14 . All these health issues are also concerns among pilots, cabin crews, and passengers 15–17 .…”
Section: Introductionmentioning
confidence: 99%
“…MVOCs is suggested to be associated with asthma development and other respiratory symptoms, [8][9][10] rhinitis, eye irritation, skin itching and redness, headache, and tiredness. [11][12][13][14] All these health issues are also concerns among pilots, cabin crews, and passengers. [15][16][17] Thus, it is important to characterize the microbial composition and related environmental characteristics in commercial flights.…”
mentioning
confidence: 99%
“…Based on international research data, it is known that living or working in a building with moisture damage can cause asthma, asthma exacerbation, allergic alveolitis, and increased susceptibility to infection. Other symptoms have also been described, e.g., eye, ear, and skin irritation [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. According to a recent review by the California Public Health Organization [17], there is a sufficiently strong relationship between moisture and mold damage and the risk for respiratory problems and asthmatic attacks to prove causality.…”
Section: Introductionmentioning
confidence: 99%